Wage bargaining and management opposition in the presence of productivity gains and organization costs - Arno Riedl (Institute for Advanced Studies (IHS), 1997)
Empirical studies have emphasized three important factors in firm-labor relationships: (a) organization costs of workers, (b) management opposition against workers' organizing drives, (c) the possibility of productivity enhancing effects due to voice/response reasons. In this paper the interplay of all three issues is simultaneously analyzed. The possibility of forgone productivity gains puts an upper bound on management opposition against organizing drives of the workers, even if management opposition is cost-less. Strategic gift exchange - less opposition for higher productivity - plays a crucial role. Decreasing productivity gains and increasing the firm's bargaining power lowers management opposition. The equilibrium wage is above the workers' reservation wage.
Keywords: C78; J50; J51; 330; wage bargaining; management opposition; productivity gains; organization costs; Lohnverhandlungstheorie; Gewerkschaftsmitgliedschaft; Betriebsrat; Management; Theorie